Ahmed Glaucoma Valves versus EX-PRESS Devices in Glaucoma Secondary to Silicone Oil Emulsification - Zhuyun Qian; Kai Xu; Xiangmei Kong; Huan Xu (Journal of Ophthalmology)
Objective. To evaluate and compare the clinical effects of Ahmed glaucoma valves (AGVs) and EX-PRESS implants on glaucoma secondary to silicone oil (SO) emulsification. Methods. A retrospective case-series study was designed. A total of 23 eyes with late intraocular pressure (IOP) elevation secondary to SO emulsification were included in the study. Antiglaucoma surgery with implantation of AGVs or EX-PRESS devices was performed. Pre- and postoperative ocular parameters were recorded at each visit during a 1-year follow-up period. The rates of complete success (IOP < 21 mmHg without medication) and qualified success (IOP < 21 mmHg with ≤3 glaucoma medications) were analyzed. Results. A total of 14 eyes underwent AGV implantation, and 9 underwent EX-PRESS implantation. The mean IOP and number of medications used at the last follow-up decreased significantly compared with that before surgery (P<0.001). The total success rate for all eyes including complete success (7/23) and qualified success (7/23) was 60.9% (14/23) at 1 year. The total success rate in the AGV group was 78.6% (11/14), whereas it was 33.3% (3/9) in the EX-PRESS group; the difference between the 2 groups was significant (P<0.05). Conclusion. For glaucoma secondary to SO emulsification, glaucoma implants could be effective at lowering IOP, and AGVs might produce better outcomes than EX-PRESS devices.